Debt Tax Shields Around the OECD World. Issue 1 (2nd January 2017) - Castillo, Augusto; Niño, Jorge; Zurita, Salvador
ABSTRACT: Taxes affect a company's optimal capital structure, value, and cost of capital, but their impact depends on the tax regime of the country where the company operates. The OECD classifies the tax regimes of its member countries in seven groups. In this paper we offer a general model that encompasses those seven groups. We show that tax benefits of debt vary significantly across tax systems, and that using either Modigliani and Miller's (1963) or Miller's (1977) formulas in other tax regimes can lead to quantitatively important mistakes. We also find a significantly positive relationship between average leverage in OECD countries and our indicator of tax shields.